PENGARUH DANA PIHAK KETIGA (DPK), RISIKO LIKUIDITAS DAN RISIKO PEMBIAYAAN TERHADAP PROFITABILITAS BSI KCP GAJAH MADA: LITERATURE REVIEW - Sriyono, Sriyono; Tri Tungga Dewi, Ayu; Nurul Hidayati, Fitriana; Rahma Maulida, Reva (Penerbit Lafadz Jaya, 2023)
Sharia banks are an integral part of the world's financial system which is experiencing very rapid development so that it has a fairly high level of profitability. So if the higher the profitability of a bank, the better its performance will be. The level of profitability of a bank is influenced by several factors, for example due to the presence of third party funds (DPK), Liquidity Risk and Financing Risk. The design of this research is a Literature Review or literature review. Database searches using Google Scholar from 2020 to 2024. Secondary data sources in this research refer to books, scientific reports, articles from previous research. Search results on Google Scholar with the keywords